Языковая концептуализация обиды: вариации на тему одной из работ И.И. Срезневского - Савченко, Л.Р. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2012)
До 200-річчя від дня народження академіка Ізмаїла Івановича Срезнєвського. В статье осуществляется реконструкция национально-специфических смыслов концепта ОБИДА на фоне сопоставления с украинскими словами ОБРАЗА, ОБРАЗИТИ. Особое внимание уделяется этимонам соответствующие слов. The study focuses on the reconstruction of cross-cultural roots of the word ”offence.” The study is performed to compare the Russian word to its Ukrainian counterparts, such as “resentment” and “to insult.” Particular attention is paid to etymons of the corresponding words.
Linguistic conceptualization of the notion “offence”: variations on a theme from a work by Izmail Sreznevsky
Савченко Людмила Ростиславівна, канд. філол. наук, доцент кафедри російської мови Харківського національного університету імені В. Н. Каразіна
Keywords: etymon; internal form of a word; notion; discourse; narration; этимон; внутренняя форма; концепт; дискурс; нарратив